Genetic Diversity of a Natural Population of Akebia trifoliata (Thunb.) Koidz and Extraction of a Core Collection Using Simple Sequence Repeat Markers - Zhong, Yicheng; Wang, Yue; Sun, Zhimin; Niu, Juan; Shi, Yaliang; Huang, Kunyong; Chen, Jing; Chen, Jianhua; Luan, Mingbao (Frontiers in Genetics, 2021)
Understand genetic diversity and genetic structure of germplasm is premise of germplasm conservation and utilization. And core collection can reduce the cost and difficulty of germplasm conservation. Akebia trifoliata (Thunb.) Koidz is an important medicinal, fruit and oil crop, particularly in China. In this study, 28 simple sequence repeat (SSR) markers were used to assess the genetic diversity and genetic structure of 955 A. trifoliata germplasms, determine their molecular identity and extract a core collection. The genetic diversity of the 955 germplasms was moderately polymorphic. The average number of alleles (Na), observed heterozygosity (HO), expected heterozygosity (HE), Shannon’s information index (I∗), and polymorphic information content (PIC) were 3.71, 0.24, 0.46, 0.81, and 0.41, respectively. Four subpopulations were identified, indicating a weak genetic structure. A 955 germplasms could be completely distinguished by the characters of s28, s25, s74, s89, s68, s30, s13, s100, s72, s77, and s3. And each germplasm’s molecular identity was made up of eleven characters. The core collection was composed of 164 germplasms (17.2% of 955 total germplasms in the population) and diversity parameters differed significantly from those of a random core collection. These results have implications for germplasm conservation. At the same time, based on the results, the 955 germplasm could be better used and managed.